INFÂNCIA CONTEMPORÂNEA: AS MANIFESTAÇÕES TELEVISIVAS NAS CULTURAS LÚDICAS - Jéssika Naiara da Silva; José Milton de Lima; Leonardo de Angelo Orlandi; Susana Angelin Furlan (Universidade do Oeste Paulista, 2012)
This study took as its central objective to analyze how the media, especially television, were present in the daily lives of children in a kindergarten institution in the city of Álvares Machado-SP. Whereas parents / guardians and educators play a key role in mediating culture, research has attempted placements that can be made against the issue to a quality education. This process aims to collaborate in forming citizens more aware, critical, autonomous. The research is supported by the theoretical Historic-Cultural Theory, Sociology of Childhood and author of Social Communication. The methodology is qualitative in nature, characterized as Ethnographic Research. The results showed that the children have direct contact with the television and that programming preferred them are: the cartoon, programs, soap operas and movies. This relationship is manifested in cultures playful children's clothes, shoes, backpacks and objects.